2021
DOI: 10.3390/antiox10050752
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Mellitus in the SARS-CoV-2 Pandemic: Oxidative Stress as a Major Pathophysiological Mechanism Linked to Adverse Clinical Outcomes

Abstract: Recent reports have demonstrated the association between type 1 diabetes mellitus (T1DM) and increased morbidity and mortality rates during coronavirus disease (COVID-19) infection, setting a priority of these patients for vaccination. Impaired innate and adaptive immunity observed in T1DM seem to play a major role. Severe, life-threatening COVID-19 disease is characterized by the excessive release of pro-inflammatory cytokines, known as a “cytokine storm”. Patients with T1DM present elevated levels of cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 167 publications
(200 reference statements)
0
18
0
3
Order By: Relevance
“…The viral protein Spike interaction with ACE2 leads to an excessive production of angiotensin II (Ang II) and activation of NADPH oxidase which subsequently results in enhancing oxidative stress mechanisms (in contrast to what happens during other viral infections) but also releasing inflammatory molecules [ 59 ]. In the course of SARS-CoV-2 infection, angiontensin II availability is increased through the high affinity and resulting binding the virus to ACE2 [ 60 ]. ACE2 in SARS-CoV-infected cells has been shown to be also involved in postinfection regulation, including immune response, viral genome replication, and cytokine secretion [ 61 ].…”
Section: Ros and Rns Generation In Sars Mers And Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The viral protein Spike interaction with ACE2 leads to an excessive production of angiotensin II (Ang II) and activation of NADPH oxidase which subsequently results in enhancing oxidative stress mechanisms (in contrast to what happens during other viral infections) but also releasing inflammatory molecules [ 59 ]. In the course of SARS-CoV-2 infection, angiontensin II availability is increased through the high affinity and resulting binding the virus to ACE2 [ 60 ]. ACE2 in SARS-CoV-infected cells has been shown to be also involved in postinfection regulation, including immune response, viral genome replication, and cytokine secretion [ 61 ].…”
Section: Ros and Rns Generation In Sars Mers And Covid-19mentioning
confidence: 99%
“…The viral [59]. In the course of SARS-CoV-2 infection, angiontensin II availability is increased through the high affinity and resulting binding the virus to ACE2 [60]. ACE2 in SARS-CoV-infected cells has been shown to be also involved in postinfection regulation, including immune response, viral genome replication, and cytokine secretion [61].…”
Section: Ros and Rns Generation In Sars Mers And Covid-19mentioning
confidence: 99%
“…Diabetes is considered to be one of the major indicators for severe COVID-19 prognosis, as more diabetic patients (diabetes type-2 is mainly evident, with limited evidence from diabetes Type-1) showed severe COVID-19 symptoms and deaths after exposure to SARS-CoV-2 virus [1,[13][14][15]. A meta-analysis concluded that the diabetic patients showed a 200% increased probability of death with severe COVID-19 symptoms than non-diabetic patients [16].…”
Section: Is Oxidative Stress a Major Cause Of Diabetes-induced Kidney...mentioning
confidence: 99%
“…Together these enzymes produce excess ROS and can be the causative agent(s) for diabetes-like diseases [18]. Another recent study reported that presence of diabetes mellitus type 1 results in increased morbidity and mortality rates during coronavirus (COVID-19) disease [13]. Diabetic patients displayed higher cell counts of leukocytes and neutrophils in their blood during admission with comparatively severe COVID-19 symptoms than non-diabetic patients.…”
Section: Is Oxidative Stress a Major Cause Of Diabetes-induced Kidney...mentioning
confidence: 99%
“…[5][6][7] In addition, the pathophysiological mechanisms linked to adverse clinical outcomes in Covid-19 affected T1D patients are just beginning to get elucidated. 8 However, several facets of Covid-related T1D are still not well understood. A recent systematic review that included 15 original investigative studies on the association between Covid-19 and T1D reported wide variability in the studied outcomes such as the length of hospital stay, need for hospitalization and intensive care, DKA rates, and severe hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%